2021
DOI: 10.1177/1591019921995334
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of intracranial aneurysms from stent-induced straightening of parent vessels by stent-assisted coiling embolization

Abstract: Background Straightening of parent vessels happens for stent-assisted coiling embolization (SACE) treatment of intracranial aneurysms. This study aims to investigate aneurysmal hemodynamic modifications caused by stent-induced vessel straightening. Methods Stent and coil deployments of a SACE-treated distal bifurcation aneurysm by finite element method were performed first with the preoperative (not straightened, NS) and postoperative (straightened, S) vessel models respectively. Computational fluid dynamics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Stents were initially used in EVT to prevent the coils from slipping out but were found in clinical trials to straighten the parent artery and cause a corresponding change in the aneurysm sac, thereby altering aneurysm hemodynamics [24]. In sidewall aneurysms, the use of stents has previously been shown to block the inflow of flow and thereby reduce the corresponding hemodynamics [25], but in bifurcation aneurysms, it has been argued that stents may produce a greater inertial force resulting from narrowed inflow jet, which enhances flow into the aneurysms [26].…”
Section: Discussionmentioning
confidence: 99%
“…Stents were initially used in EVT to prevent the coils from slipping out but were found in clinical trials to straighten the parent artery and cause a corresponding change in the aneurysm sac, thereby altering aneurysm hemodynamics [24]. In sidewall aneurysms, the use of stents has previously been shown to block the inflow of flow and thereby reduce the corresponding hemodynamics [25], but in bifurcation aneurysms, it has been argued that stents may produce a greater inertial force resulting from narrowed inflow jet, which enhances flow into the aneurysms [26].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al ( 30 ) reported an outer curve aneurysm with lower vascular tortuosity was more similar to a bifurcation aneurysm and more likely to recur. Leng et al ( 31 ) and Wan et al ( 32 ) both pointed out that better hemodynamic changes can be achieved by using stents to straighten blood vessels. The risk of recurrence can be reduced by weakening the hemodynamic characteristics of bifurcation aneurysms, which was also consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, the surface-based aneurysm and vessel geometry model with the 3D representation of the stent were used for the subsequent CFD analysis. The exact method can be referenced in our previous study ( 7 ). The FEM simulations matched the actual stent-deployment images, including the parent artery straightening ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the stent has a scaffold function and can induce angular deformation of parent arteries in the intracranial bifurcation aneurysms (2)(3)(4). It can migrate the flow impingement away from the aneurysm neck to decrease recurrence (5)(6)(7). Meanwhile, a stent with its mesh has a flow diverter effect by reducing the WSS and velocity of the aneurysm sac (8).…”
Section: Introductionmentioning
confidence: 99%